2008
DOI: 10.1016/j.jneumeth.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing synaptic conductance fluctuations in cortical neurons and their influence on spike generation

Abstract: Cortical neurons are subject to sustained and irregular synaptic activity which causes important fluctuations of the membrane potential (V m ). We review here different methods to characterize this activity and its impact on spike generation. The simplified, fluctuating point-conductance model of synaptic activity provides the starting point of a variety of methods for the analysis of intracellular V m recordings. In this model, the synaptic excitatory and inhibitory conductances are described by Gaussian-dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 71 publications
(128 reference statements)
1
51
0
Order By: Relevance
“…The fi nding that the gain and responsiveness of neurons are enhanced by synaptic noise was fi rst reported from modeling studies (Hô and Destexhe, 2000 ), and then investigated experimentally using dynamicclamp injection of in vivo-like synaptic noise (Destexhe et al, 2001 ;Chance et al, 2002 ;Fellous et al, 2003 ;Prescott and De Koninck, 2003 ;Shu et al, 2003 ;Wolfart et al, 2005 ;Higgs et al, 2006 ;Piwkowska et al, 2008 ), thus confi rming some of the predictions formulated by models. A fascinating possible consequence is that the enhanced responsiveness due to synaptic noise could be used as an attentional mechanism (Hô and Destexhe, 2000 ;Shu et al, 2003 ).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The fi nding that the gain and responsiveness of neurons are enhanced by synaptic noise was fi rst reported from modeling studies (Hô and Destexhe, 2000 ), and then investigated experimentally using dynamicclamp injection of in vivo-like synaptic noise (Destexhe et al, 2001 ;Chance et al, 2002 ;Fellous et al, 2003 ;Prescott and De Koninck, 2003 ;Shu et al, 2003 ;Wolfart et al, 2005 ;Higgs et al, 2006 ;Piwkowska et al, 2008 ), thus confi rming some of the predictions formulated by models. A fascinating possible consequence is that the enhanced responsiveness due to synaptic noise could be used as an attentional mechanism (Hô and Destexhe, 2000 ;Shu et al, 2003 ).…”
Section: Discussionmentioning
confidence: 90%
“…These quantities are evaluated from the sole knowledge of the V m activity, which makes it applicable to standard intracellular recording conditions. In the past years, each of these methods was tested using computational models, as well as in real neurons using the dynamicclamp technique (reviewed in Piwkowska et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is possible to follow a similar maximum-likelihood procedure by explicitly including fast voltagedependent conductances in the model. The VmT method also requires knowledge of the passive parameters of the recorded neuron (G L , C...) which may be difficult to obtain in vivo (see Piwkowska et al, 2008 for a discussion of this point).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the amount of correlations in the inhibitory background inputs (not belonging to the assembly, and modeled by the standard deviation of the inhibitory noise) controls the firing rate of individual cells in the assembly. Recent evidence has highlighted the predominant role of inhibition during reverberatory activity in vitro and in vivo (Piwkowska et al, 2008). The firing of the cells during the reverberation triggers slow intracellular calcium accumulation and activates calcium-dependent potassium currents.…”
Section: Regulation Of Reverberatory Activity Level By Inhibitionmentioning
confidence: 99%